Key characteristics of basal cell carcinoma with large subclinical extension. (26th November 2019) - Greywal, T.; Goldenberg, A.; Eimpunth, S.; Jiang, S.B.
Abstract: Background: Basal cell carcinoma with large subclinical extension (BCC‐LSE) is a tumour whose extensive spread becomes apparent during Mohs surgery histopathology review. Not recognizing BCC‐LSE preoperatively may result in a greater number of Mohs layers and in larger than anticipated postoperative defects. Objective: To evaluate the characteristics of BCC‐LSE. Methods: This retrospective study reviewed BCC treated with Mohs surgery at a single academic surgical centre between March 2007 and February 2012. A total of 2044 cases met the criteria of BCC‐LSE, which was defined as a lesion requiring at least three Mohs stages and a final surgical margin (difference between preoperative and postoperative measurements in either vertical or horizontal dimensions) of ≥1 cm. Results: In adjusted multivariable analysis, male sex ( P = 0.05), Fitzpatrick skin type I ( P = 0.002), history of prior BCC ( P = 0.003) and subtypes of basosquamous, metatypical, micronodular, infiltrative, morpheaform and sclerosing ( P = 0.005) remained significant BCC‐LSE predictors. Conclusions: Demographic factors, including personal history of BCC, skin type, anatomic location, gender and age, in addition to tumour histologic subtype assessed through incisional biopsy, can help predict occurrence of BCC‐LSE and assist physicians in optimizing preoperative assessment of surgical time and complexity.